Effects of forearm fatigue on tennis serving - Lo, K. C.; Lee, S. H.; Wang, L. H.; Su, F. C. (14th International Symposium on 3D Analysis of Human Movement, 2016)
The impact of fatigue includes the reduction of muscle force output and the decrease in the muscle contraction, ball speed, and muscle power. The primary goal was to determine the effect of fatigue on the forearm muscle control over tennis serving. Twelve tennis players performed required serving tasks. The results showed a significant difference in pre- and post-fatigue on wrist ulnar deviation angle (P = 0.02) in impact. Extensor carpi radials muscle activity showed a significant difference during the cocking phase, with a peak value during post-fatigue flat serve (P = 0.02). Local fatigue did influence the tennis server`s ability to control the ball into the specific area.